Clinicopathological value of epidermal growth factor receptor (EGFR) and Ki-67 expression in colorectal adenoma and adenocarcinoma - Eman Mohamed Ahmed Nor; Eman Mohamed Saied; Samir Nemr Mina; Mohamed Mostafa Shareef; Dareen Mohamed Abdelaziz (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate epidermal growth factor receptor and Ki-67 immunohistochemical expression in colorectal adenoma and carcinoma cases, and to relate their expression with the available clinicopathological data. Methods: The retrospective study was conducted at the Faculty of Medicine, Kafrelsheikh University, Egypt, from September 2019 to October 2020, and comprised formalin-fixed and paraffin-embedded specimens related to cases of colorectal adenoma and those of colorectal carcinoma, who had no previous radiation or chemotherapeutic treatment. Immunohistochemical staining of all thecases was done using anti-epidermal growth factor receptor and anti-Ki-67 antibodies. Data was analysed using SPSS 20. Results: Of the 70 cases, 20(28.5%) were of colorectal adenoma; mean age 52.95±13.47 years, and male-to-female ratio 1:1. The remaining 50(71.5%) cases had colorectal carcinoma; mean age 51.08±13.49 years, and male-to-female ratio 1.17:1. Epidermal growth factor receptor and Ki-67 overexpression related significantly to villous histopathological type and high-grade dysplasia in colorectal adenoma cases (p<0.05). In colorectal carcinoma cases, epidermal growth factor receptor overexpression related significantly to tumour grade (p<0.05). Ki-67 overexpression related significantly to increased pathological stage (p<0.05). Conclusions: Overexpression of epidermal growth factor receptor and Ki-67 was found to be an ominous sign of colorectal adenoma aggressiveness, and the risk of progression to colorectal carcinoma. Keywords: Antigen, Adenoma, Colorectal neoplasms, Receptors, Carcinoma.